2007
DOI: 10.1002/jmri.21034
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic T1 mapping predicts outcome of chemoradiation therapy in primary rectal carcinoma: Sequence implementation and data analysis

Abstract: Purpose:To describe details about the implementation of a dynamic T 1 -mapping technique and a simple data analysis strategy that can be used to predict therapy outcome in primary rectal carcinoma and to investigate the physiologic meaning of the obtained parameter. Materials and Methods:Contrast-enhanced dynamic T 1 mapping was achieved with a snapshot fast low-angle shot (FLASH) T 1 mapping sequence implemented on a 1.5T MR scanner. This method was applied to 58 patients with primary rectal cancer before ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…They showed the possible role of an increased angiogenic activity in aggressive tumour cell clusters that resulted in reduced nutrient supply and higher fraction of intratumoral necrosis. In line with these results, the same researchers published another paper (Kremser et al, 2007) in which they examined, using similar methodology, 58 patients before chemo-radiotherapy . Once again they found that PI is a good predictor of therapy outcome, being, before therapy, the PI of non-responders lower than responders.…”
Section: Dce-mri In Rectal Cancermentioning
confidence: 73%
See 4 more Smart Citations
“…They showed the possible role of an increased angiogenic activity in aggressive tumour cell clusters that resulted in reduced nutrient supply and higher fraction of intratumoral necrosis. In line with these results, the same researchers published another paper (Kremser et al, 2007) in which they examined, using similar methodology, 58 patients before chemo-radiotherapy . Once again they found that PI is a good predictor of therapy outcome, being, before therapy, the PI of non-responders lower than responders.…”
Section: Dce-mri In Rectal Cancermentioning
confidence: 73%
“…For example, Henderson et al (1998) found that this interval should be approximately less than 16 s in the case of breast DCE-MRI. In the wash-out phase, this requirement could be relaxed (de Vries et al, 2003;Kremser et al, 2007). A high temporal resolution can be difficult to obtain because the acquisition of a single volume could require several seconds as a large part of the whole abdomen is scanned.…”
Section: Spatial and Temporal Resolutionmentioning
confidence: 99%
See 3 more Smart Citations